Lithium iron phosphate positive electrode material and preparation method thereof
By covering the carbon material shell layer on the surface of the core layer of the lithium iron phosphate, optimize the ratio of SLI/SC and SC/SO, solve the problem of low lithium iconic iconic lithium content of lithium iron phosphate, increase the battery charging ratio capacity And cycle life.
Patent Information
- Application Number
- CN202411683466.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-01-21
AI Technical Summary
The existing lithium iron phosphate positive electrode materials have low active lithium content, resulting in low charging specific capacity, affecting the cycle life and capacity retention rate of the battery.
The surface of carbon material containing carbon, oxygen and lithium elements on the surface of lithium iron phosphate core layer is covered, and the ratio of SLI/SC and SC/SO is tested through the XPS surface element test to optimize the structure and composition of lithium iron phosphate positive material materials Essence
The conductivity and active lithium release capability of the lithium iron phosphate cathode material are improved, the charging specific capacity and cycle life of the battery are enhanced, and the processing performance of the battery is improved.
Smart Images

Figure BDA0005149167170000081 
Figure BDA0005149167170000082 
Figure BDA0005149167170000091
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a lithium iron phosphate positive electrode material and a preparation method thereof. Background Art
[0002] Lithium iron phosphate material has the advantages of good cycle stability and high safety. It is widely used in electric vehicles, electronic products, energy storage and other fields, and has become one of the main positive electrode materials for lithium-ion batteries.
[0003] Thanks to the stability of the Fe-O octahedron and the phosphate ion PO tetrahedron in the olivine structure, the lithium iron phosphate material is not prone to structural collapse during multiple lithium insertion and delithiation cycles, thus being able to support a very high cycle life. However, in lithium-ion batteries composed of lithium iron phosphate and graphite, active lithium will be lost as the battery is charged and discharged, and "dead lithium" will be deposited on the electrode surface through side reactions in the battery, causing a decrease in the battery capacity retention rate.
[0004] Therefore, there is an urgent need to provide a lithium iron phosphate positive electrode material with high active lithium content and high charge specific capacity. Summary of the invention
[0005] The main purpose of the present invention is to provide a lithium iron phosphate positive electrode material and a preparation method thereof, so as to solve the problems of low active lithium content and low charging specific capacity of the lithium iron phosphate positive electrode material in the prior art.
[0006] In order to achieve the above-mentioned object, according to a first aspect of the present invention, a lithium iron phosphate positive electrode material is provided, comprising a core layer and a shell layer, wherein the material of the core layer comprises a lithium iron phosphate material, the shell layer at least partially covers the surface of the core layer, and the material of the shell layer comprises a carbon material, wherein the carbon material contains carbon, oxygen and lithium; XPS is used to test the surface elements of the lithium iron phosphate positive electrode material, and 5%<S Li / S C <10%,50%<S C / S O <70%, among which S Li is the area of the characteristic peak of lithium, S C is the area of the characteristic peak of carbon element, S O is the area of the characteristic peak of oxygen element.
[0007] Furthermore, in the lithium iron phosphate positive electrode material, the mass content of carbon element is 0.9% to 2.5%.
[0008] Furthermore, the chemical formula of lithium iron phosphate material is Li 1+x Fe 1-y M yPO4, wherein 0.03≤x<0.1, 0≤y≤0.02, and M is selected from at least one of Ti, Mg, Zr, V, and Mn.
[0009] Furthermore, the D50 particle size of the lithium iron phosphate positive electrode material is 0.5 to 2 μm.
[0010] Furthermore, the specific surface area of the lithium iron phosphate cathode material is 5 to 25 m 2 / g.
[0011] According to a second aspect of the present invention, there is provided a method for preparing a lithium iron phosphate positive electrode material, comprising the following steps:
[0012] S1, mixing a phosphorus source, an iron source, an M source, a first lithium source, and a first carbon source to obtain a first material; M is selected from at least one of Ti, Mg, Zr, V, and Mn;
[0013] S2, performing a first sintering and crushing on the first material to obtain a second material;
[0014] S3, mixing the second lithium source and the second carbon source to produce a coordination reaction to obtain a third material; the second carbon source is a polymer containing oxygen atoms;
[0015] S4, mixing the second material and the third material, performing a second sintering, and crushing to obtain a lithium iron phosphate positive electrode material;
[0016] The lithium iron phosphate positive electrode material comprises a core layer and a shell layer, wherein the material of the core layer comprises lithium iron phosphate material, the shell layer at least partially covers the surface of the core layer, and the material of the shell layer comprises a carbon material, wherein the carbon material contains carbon, oxygen and lithium elements; XPS is used to test the surface elements of the lithium iron phosphate positive electrode material, and the result is 5%<S Li / S C <10%,50%<S C / S O <70%, among which S Li is the area of the characteristic peak of lithium, S C is the area of the characteristic peak of carbon element, S O is the area of the characteristic peak of oxygen element.
[0017] Furthermore, in S2, the conditions for the first sintering are: temperature 500-900°C, time 5-20h; in S4, the conditions for the second sintering are: temperature 300-500°C, time 5-20h.
[0018] Furthermore, in S3, the mass ratio of the lithium element in the second lithium source to the oxygen element in the second carbon source is 0.1 to 0.3.
[0019] Furthermore, in S3, the conditions of the coordination reaction are: temperature 20-50° C., time 2-10 h.
[0020] Furthermore, in S4, the mass ratio of lithium element in the third material to the second material is (0.001-0.005):1.
[0021] Furthermore, in S1, the phosphorus source, the iron source, the M source, the first lithium source, and the first carbon source are mixed, a solvent is added to form a slurry, and the slurry is ground and spray-dried to obtain the first material.
[0022] Furthermore, the first carbon source is at least one of polyethylene glycol and glucose.
[0023] Furthermore, the second carbon source is at least one of polyethylene glycol, polypropylene glycol, and polydextrose.
[0024] Furthermore, the first lithium source and the second lithium source are each independently at least one of lithium hydroxide, lithium hydroxide monohydrate, lithium oxide, and lithium carbonate.
[0025] Furthermore, the phosphorus source is at least one of ferric phosphate, diammonium phosphate, and phosphoric acid.
[0026] Furthermore, the iron source is at least one of ferric phosphate, ferric oxalate and ferric oxide.
[0027] Furthermore, the M source is at least one of an oxide containing the M element, a nitrate containing the M element, and a carbonate containing the M element, such as titanium dioxide, manganese dioxide, and the like.
[0028] By applying the technical solution of the present invention, a carbon material shell layer containing carbon, oxygen and lithium elements is provided on the surface of the lithium iron phosphate core layer, so that the conductivity of the lithium iron phosphate positive electrode material can be improved. In addition, additional active lithium can be provided, which can be released into the negative electrode during the charging process, thereby replenishing lithium, improving battery capacity and extending cycle life. In addition, by controlling the characteristic peak area ratio of lithium and carbon elements and the characteristic peak area ratio of carbon and oxygen elements, the present invention can improve the release of active lithium in the shell layer and the core layer, improve the charge specific capacity of the lithium iron phosphate positive electrode material, and improve the processing performance of the lithium iron phosphate positive electrode material. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0030] As described in the background technology of the present invention, there is a problem in the prior art that the charge and discharge specific capacity of lithium iron phosphate materials is low. In order to solve the above technical problems, in a typical embodiment of the present invention, a lithium iron phosphate positive electrode material is provided, wherein the lithium iron phosphate positive electrode material comprises a core layer and a shell layer, the material of the core layer comprises a lithium iron phosphate material, the shell layer is at least partially coated on the surface of the core layer, the material of the shell layer comprises a carbon material, and the carbon material contains carbon, oxygen and lithium elements; XPS is used to test the surface elements of the lithium iron phosphate positive electrode material, and 5% <S Li / S C <10%,50%<S C / S O <70%, among which S Li is the area of the characteristic peak of lithium, S C is the area of the characteristic peak of carbon element, S O is the area of the characteristic peak of oxygen element.
[0031] Coating the carbon material shell layer on the surface of the lithium iron phosphate core layer helps to improve the conductivity of the lithium iron phosphate positive electrode material, thereby improving the charge and discharge performance of the battery; in addition, the carbon material can reduce the ion diffusion resistance on the surface of the lithium iron phosphate material, increase the diffusion rate of lithium ions in the positive electrode material, thereby improving the charge and discharge rate of the battery; in addition, the presence of the carbon material shell layer can increase the contact area between the positive electrode material and the electrolyte, and improve the electrochemical activity of the positive electrode material; furthermore, the carbon material can prevent harmful components in the electrolyte from corroding the lithium iron phosphate material, thereby extending the battery life. In addition, the carbon material of the present invention also contains oxygen and lithium elements. By controlling the ratio of the characteristic peak areas of oxygen and lithium elements, on the one hand, the content of active lithium in the lithium iron phosphate positive electrode material can be increased, and its charge specific capacity can be increased. On the other hand, it is beneficial to improve the processing performance of the lithium ion battery prepared with the lithium iron phosphate positive electrode material, so that the comprehensive performance of the lithium ion battery is higher and has a wider range of applications. Controlling the ratio of the characteristic peak areas of carbon and oxygen elements can enhance the release activity of lithium ions in the shell and core layers, and increase the charge capacity and rate performance of lithium iron phosphate cathode materials.
[0032] In some embodiments, the carbon material is obtained by calcining an oxygen-containing polymer carbon source and a lithium source, and Li-O coordination bonds exist in the carbon material.
[0033] The presence of Li-O coordination bonds helps to improve the dispersion of metal ions, and can decompose during the subsequent charging process to release active lithium ions and increase the charging capacity.
[0034] In some embodiments, the mass content of carbon in the lithium iron phosphate positive electrode material is 0.9% to 2.5%; preferably, the mass content of carbon is 1% to 2%.
[0035] Controlling the mass content of carbon elements is, on the one hand, to achieve effective electron conduction between particles and improve energy efficiency; on the other hand, it is to increase the compaction density of the positive electrode sheet prepared with the positive electrode material and further improve the electrochemical performance of the lithium iron phosphate positive electrode material.
[0036] In some embodiments, the chemical formula of the lithium iron phosphate material is Li 1+x Fe 1-y M y PO4, wherein 0.02≤x<0.1, 0≤y≤0.02, and M is selected from at least one of Ti, Mg, Zr, V, and Mn.
[0037] The above-mentioned limitation on the chemical formula of lithium iron phosphate material is to effectively improve its charge capacity, discharge capacity and cycle performance while ensuring that the lithium iron phosphate positive electrode material has high safety.
[0038] In some embodiments, the D50 particle size of the lithium iron phosphate positive electrode material is 0.5 to 2 μm.
[0039] When the D50 particle size of the lithium iron phosphate positive electrode material falls within the above range, the compaction density of the lithium iron phosphate positive electrode material can be increased to 2.35 g / cm 3 The above helps to improve the volume energy density of lithium-ion batteries using the material, while ensuring that the battery made with the lithium iron phosphate positive electrode material has good rate performance.
[0040] In some embodiments, the specific surface area of the lithium iron phosphate positive electrode material is 5 to 25 m 2 / g.
[0041] The specific surface area of the lithium iron phosphate positive electrode material is controlled in order to ensure the processing performance of the positive electrode slurry prepared with the lithium iron phosphate positive electrode material and to improve the rate performance of the positive electrode material.
[0042] In another typical embodiment of the present invention, a method for preparing a lithium iron phosphate positive electrode material is provided, comprising the following steps:
[0043] S1, mixing a phosphorus source, an iron source, an M source, a first lithium source, and a first carbon source to obtain a first material; M is selected from at least one of Ti, Mg, Zr, V, and Mn;
[0044] S2, performing a first sintering and crushing on the first material to obtain a second material;
[0045] S3, mixing the second lithium source and the second carbon source to produce a coordination reaction to obtain a third material; the second carbon source is a polymer containing oxygen atoms;
[0046] S4, mixing the second material and the third material, performing a second sintering, and crushing to obtain a lithium iron phosphate positive electrode material;
[0047] The lithium iron phosphate positive electrode material comprises a core layer and a shell layer, wherein the material of the core layer comprises lithium iron phosphate material, the shell layer at least partially covers the surface of the core layer, and the material of the shell layer comprises a carbon material, wherein the carbon material contains carbon, oxygen and lithium elements; XPS is used to test the surface elements of the lithium iron phosphate positive electrode material, and the result is 5%<S Li / S C <10%,50%<S C / S O <70%, among which S Li is the area of the characteristic peak of lithium, S C is the area of the characteristic peak of carbon element, S O is the area of the characteristic peak of oxygen element.
[0048] In S1, the first carbon source is added as a reducing agent into the raw material, and the lithium iron phosphate material is prepared by using the phosphorus source, the iron source, the M source, the first lithium source, and the first carbon source. The lithium iron phosphate material is used as the core layer material in the lithium iron phosphate positive electrode material of the present invention, and is an essential component of the lithium iron phosphate positive electrode material, which can provide good cycle stability; in S3, the second lithium source and the second carbon source are mixed to form a carbon material shell layer on the surface of the lithium iron phosphate material, which has the effect of improving conductivity and replenishing lithium; this method can produce 5%<S Li / S C <10%、50%<S C / S O The lithium iron phosphate positive electrode material with a capacity less than 70% has high charge specific capacity and discharge specific capacity.
[0049] In some embodiments, 6% < S Li / S C <9%,52%<S C / S O <56%. Li / S C and S C / S O The value of is further optimized, and the positive electrode sheet prepared with the lithium iron phosphate positive electrode material has a higher compaction density and has good charge and discharge specific capacity and rate performance.
[0050] In some embodiments, in S2, the conditions for the first sintering are: temperature 500-900°C, time 5-20 hours; in S4, the conditions for the second sintering are: temperature 300-500°C, time 5-20 hours. The first sintering and the second sintering are performed under an inert atmosphere. Preferably, the inert atmosphere includes at least one of nitrogen, argon, and helium.
[0051] The lithium iron phosphate positive electrode material obtained by sintering under the above conditions has good structural stability and high electrochemical activity.
[0052] In some embodiments, in S3, the mass ratio of the lithium element in the second lithium source to the oxygen element in the second carbon source is 0.1 to 0.3; the conditions of the coordination reaction are: temperature 25 to 50° C., time 2 to 10 h.
[0053] The preparation conditions in S3 are controlled within the above range in order to allow the presence of Li-O coordination bonds in the third material, so that a highly dispersed Li-O structure surrounded by carbon elements can be formed during the subsequent sintering process, and more active lithium ions can be released during the charging process, thereby improving the charging specific capacity.
[0054] In some embodiments, in S4, the mass ratio of lithium element in the third material to the second material is (0.001-0.005):1.
[0055] The purpose of controlling the above mass ratio is to form a carbon material shell layer of appropriate thickness on the surface of the lithium iron phosphate positive electrode material. On the one hand, it is beneficial to improve the conductivity of the lithium iron phosphate positive electrode material and increase the active lithium content. On the other hand, it is beneficial to increase the migration rate of lithium ions in the core layer of the positive electrode material and improve its rate performance.
[0056] In some embodiments, in S1, the phosphorus source, the iron source, the M source, the first lithium source, and the first carbon source are mixed, and then a solvent is added to form a slurry, which is then ground and spray-dried to obtain the first material. The first material formed by this method has good component uniformity.
[0057] In some embodiments, in S1, the D50 particle size of the ground particles is 0.3-1.5 μm.
[0058] In some embodiments, in S2, air flow milling is used to perform milling, so that more than 90% of the particles in the second material exist in the form of single particles.
[0059] The particle size and particle morphology of the first material and the second material have a certain influence on the particle size of the subsequent product. By controlling the D50 particle size of the first material and the particle morphology of the second material within the above range, a lithium iron phosphate positive electrode material with a D50 particle size of 0.5μm to 2μm can be prepared, which is conducive to the preparation of a positive electrode sheet with a higher compaction density.
[0060] In some embodiments, the first carbon source is at least one of polyethylene glycol and glucose.
[0061] Using the above components as the first carbon source can play a good reducing role to form a lithium iron phosphate material with higher purity, which has good electrochemical properties.
[0062] In some embodiments, the second carbon source is at least one of polyethylene glycol, polypropylene glycol, and polydextrose.
[0063] Selecting the above components as the second carbon source can cause a coordination reaction with the lithium source to form a carbon coating layer containing Li-O coordination bonds, which can improve the conductivity of the lithium iron phosphate positive electrode material on the one hand, and release active lithium ions during the subsequent charge and discharge process on the other hand, thereby increasing the charging capacity.
[0064] In some embodiments, the first lithium source and the second lithium source are each independently at least one of lithium hydroxide, lithium hydroxide monohydrate, lithium oxide, and lithium carbonate.
[0065] In some embodiments, the phosphorus source is at least one of ferric phosphate, diammonium phosphate, and phosphoric acid.
[0066] In some embodiments, the iron source is at least one of ferric phosphate, ferric oxalate, and ferric oxide.
[0067] In some embodiments, the M source is at least one of an oxide containing the M element, a nitrate containing the M element, and a carbonate containing the M element. The oxide containing the M element may be titanium dioxide, manganese dioxide, etc., the nitrate containing the M element may be magnesium nitrate, etc., and the carbonate containing the M element may be magnesium carbonate, etc.
[0068] By preparing lithium iron phosphate positive electrode material using the preparation method in the embodiment of the present invention, the above-mentioned selection of the types of the first carbon source, the second carbon source, the first lithium source, the second lithium source, the phosphorus source, the iron source, and the M source can prepare a positive electrode material with good charge and discharge specific capacity and rate performance.
[0069] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0070] Example 1
[0071] An embodiment of the lithium iron phosphate positive electrode material of the present invention, the preparation method of the lithium iron phosphate positive electrode material in this embodiment comprises the following steps:
[0072] S1, mixing iron phosphate, lithium carbonate and nano titanium dioxide in a molar ratio of 2:1.03:0.002, adding the mixture into water to prepare a first slurry with a solid content of 20%, adding polyethylene glycol accounting for 0.6% by mass of the first slurry and glucose accounting for 0.7% by mass of the first slurry into the obtained first slurry, stirring and dissolving the mixture to obtain a second slurry, ball-milling the solid in the second slurry to a particle size of 0.4 μm at D50, and spray drying the mixture at 250° C. to obtain a first material;
[0073] S2, placing the first material in a sintering furnace cavity under a nitrogen atmosphere, heating to 750° C. at a heating rate of 5° C. / min and keeping the temperature for 12 hours, and crushing the material by air flow crushing after natural cooling to obtain a second material in which more than 90% of the particles are in the form of single particles;
[0074] S3, mixing lithium hydroxide monohydrate and polyethylene glycol in a mass ratio of 1:4 (the mass ratio of lithium element in lithium hydroxide monohydrate to oxygen element in polyethylene glycol is 0.1141), stirring at 45° C. for 120 min, and performing coordination reaction to obtain a third material;
[0075] S4, mixing the second material and the third material in a mass ratio of 1:0.06 (the mass ratio of lithium element in the third material to the second material is 0.00188:1), and then heating to 350°C at a heating rate of 5°C / min in a nitrogen atmosphere, and keeping the temperature for 8 hours to obtain a lithium iron phosphate positive electrode material.
[0076] Example 2
[0077] An embodiment of the lithium iron phosphate positive electrode material of the present invention. The difference between the preparation method of the lithium iron phosphate positive electrode material described in this embodiment and that in Example 1 is that in S3, the mass ratio of lithium hydroxide monohydrate and polyethylene glycol is 1:2 (the mass ratio of lithium element in lithium hydroxide monohydrate to oxygen element in polyethylene glycol is 0.2283); in S4, the mass ratio of the second material and the third material is 1:0.07 (the mass ratio of lithium element in the third material to the second material is 0.00362:1).
[0078] Example 3
[0079] An embodiment of the lithium iron phosphate positive electrode material of the present invention. The difference between the preparation method of the lithium iron phosphate positive electrode material described in this embodiment and that in Example 1 is that in S3, the mass ratio of lithium hydroxide monohydrate to polyethylene glycol is 3:5 (the mass ratio of lithium element in lithium hydroxide monohydrate to oxygen element in polyethylene glycol is 0.2739); in S4, the mass ratio of the second material to the third material is 1:0.08 (the mass ratio of lithium element in the third material to the second material is 0.00461:1).
[0080] Example 4
[0081] An embodiment of the lithium iron phosphate positive electrode material of the present invention. The difference between the preparation method of the lithium iron phosphate positive electrode material described in this embodiment and that in Example 1 is that in S3, the mass ratio of lithium hydroxide monohydrate to polyethylene glycol is 3:10 (the mass ratio of lithium element in lithium hydroxide monohydrate to oxygen element in polyethylene glycol is 0.1370); in S4, the mass ratio of the second material to the third material is 1:0.13 (the mass ratio of lithium element in the third material to the second material is 0.00441:1).
[0082] Example 5
[0083] An embodiment of the lithium iron phosphate positive electrode material of the present invention, the preparation method of the lithium iron phosphate positive electrode material described in this embodiment is different from that of Example 1 in that, in S1, iron phosphate is replaced by manganese iron phosphate, wherein the molar ratio of manganese element to iron element is 6:4.
[0084] Comparative Example 1
[0085] A lithium iron phosphate positive electrode material, the preparation method of which is different from that of Example 1 in that S3 and S4 are not included.
[0086] Comparative Example 2
[0087] A lithium iron phosphate positive electrode material, the preparation method of which is different from that of Example 1 in that, in S3, the mass ratio of lithium hydroxide monohydrate to polyethylene glycol is 1:10 (the mass ratio of lithium element in lithium hydroxide monohydrate to oxygen element in polyethylene glycol is 0.0457); in S4, the mass ratio of the second material to the third material is 1:0.055 (the mass ratio of lithium element in the third material to the second material is 0.00079:1).
[0088] Comparative Example 3
[0089] A lithium iron phosphate positive electrode material, the preparation method of which is different from that of Example 1 in that, in S3, the mass ratio of lithium hydroxide monohydrate and polyethylene glycol is 4:5 (the mass ratio of lithium element in lithium hydroxide monohydrate to oxygen element in polyethylene glycol is 0.3652); in S4, the mass ratio of the second material to the third material is 1:0.09 (the mass ratio of lithium element in the third material to the second material is 0.00609:1).
[0090] Comparative Example 4
[0091] A lithium iron phosphate positive electrode material, the preparation method of which is different from that of Example 1 only in that, in S3, the stirring temperature is adjusted from 45°C to 20°C.
[0092] Performance Testing
[0093] 1) Chemical formula: 8 mL of aqua regia (the volume ratio of hydrochloric acid to nitric acid is 3:1) was used to dissolve the lithium iron phosphate positive electrode material (0.3 g) prepared in the above embodiment and comparative example, and the content of different elements was measured by ICP equipment to calculate the chemical formula;
[0094] 2) Carbon content: The carbon content in the lithium iron phosphate positive electrode materials prepared in the above examples and comparative examples was measured using a carbon-sulfur analyzer;
[0095] 3) Characteristic peak area: XPS was used to perform narrow spectrum scanning of Li, C, and O elements on the lithium iron phosphate positive electrode materials prepared in the above examples and comparative examples to determine the characteristic peak areas of the corresponding elements;
[0096] 4) D50 particle size: The lithium iron phosphate positive electrode materials prepared in the above examples and comparative examples were measured using a laser particle size analyzer;
[0097] 5) Specific surface area: The specific surface area of the lithium iron phosphate positive electrode materials prepared in the above examples and comparative examples was measured using a nitrogen adsorption instrument;
[0098] 6) Charging capacity / rate performance test: The obtained positive electrode slurry is coated on aluminum foil by a transfer coater, and then dried, cold pressed, and slit to form positive electrode sheets of the required shape. The compaction density of the electrode sheets is uniformly set to 2.45g / cm 3 , surface density is set to 200g / m 2 . Use a punching machine to remove the circular positive electrode sheet (diameter 12mm) from the rolled electrode sheet, assemble it together with the lithium sheet as the negative electrode into the shell of the button battery (separated by an isolation membrane in the middle) and add electrolyte (the formula is EC:DMC:DEC=1:1:1, vinylene carbonate and lithium hexafluorophosphate are added, the mass fraction of vinylene carbonate in the electrolyte is 2%, and the molar concentration of lithium hexafluorophosphate in the electrolyte is 1mol / L). After packaging, use a charging and discharging device to charge and discharge the battery at a current of 0.373mA (charge to 3.75V, discharge to 2.0V) to determine its charge and discharge capacity. Then charge to 3.75V with a current of 0.373mA again, and discharge to 2.0V with a current of 3.73mA. The discharge capacity divided by the first discharge capacity is the rate performance. The test battery needs to be placed in a constant temperature box and the temperature is set to 25℃.
[0099] 7) Pole compaction test: After the positive electrode is rolled by a roller press to a set compaction, it is folded in half manually. After the electrode is bent until the two folded sides are completely in contact, the crease is checked. The highest compaction that can keep the crease of the electrode opaque is the ultimate compaction of the electrode.
[0100] The performance test results are shown in Tables 1 and 2.
[0101] Table 1
[0102]
[0103] Table 2
[0104]
[0105]
[0106] As shown in Tables 1 and 2, the present invention controls the S of the lithium iron phosphate positive electrode material. Li / S C , S C / S O The charging capacity of the battery made with the positive electrode material, i.e., Examples 1 to 5 of the present invention, can reach 170 mAh / g or more, can absorb electric energy faster, shorten the charging time, and can withstand more charging cycles. Li / S C and / or S C / S O It is not within the scope of the present invention and its charging capacity is low.
[0107] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A lithium iron phosphate positive electrode material, characterized in that: The invention comprises a core layer and a shell layer, wherein the material of the core layer comprises a lithium iron phosphate material, the shell layer at least partially covers the surface of the core layer, and the material of the shell layer comprises a carbon material, wherein the carbon material contains carbon, oxygen and lithium elements; XPS is used to test the surface elements of the lithium iron phosphate positive electrode material, and the result is 5%<S Li / S C <10%,50%<S C / S O <70%, among which S Li is the area of the characteristic peak of lithium, S C is the area of the characteristic peak of carbon element, S O is the area of the characteristic peak of oxygen element.
2. The lithium iron phosphate positive electrode material according to claim 1, characterized in that: The mass content of carbon element in the lithium iron phosphate positive electrode material is 0.9% to 2.5%.
3. The lithium iron phosphate positive electrode material according to claim 1 or 2, characterized in that: The chemical formula of the lithium iron phosphate material is Li 1+x Fe 1-y M y PO4, wherein 0.02≤x<0.1, 0≤y≤0.02, and M is selected from at least one of Ti, Mg, Zr, V, and Mn.
4. The lithium iron phosphate positive electrode material according to claim 3, characterized in that: The D50 particle size of the lithium iron phosphate positive electrode material is 0.5 to 2 μm; and / or the specific surface area of the lithium iron phosphate positive electrode material is 5 to 25 m 2 / g.
5. A method for preparing a lithium iron phosphate positive electrode material, characterized in that: The steps include: S1, mixing a phosphorus source, an iron source, an M source, a first lithium source, and a first carbon source to obtain a first material; M is selected from at least one of Ti, Mg, Zr, V, and Mn; S2, performing a first sintering and crushing on the first material to obtain a second material; S3, mixing a second lithium source and a second carbon source to generate a coordination reaction, thereby obtaining a third material; wherein the second carbon source is a polymer containing oxygen atoms; S4, mixing the second material and the third material, performing a second sintering, and crushing to obtain the lithium iron phosphate positive electrode material; The lithium iron phosphate positive electrode material comprises a core layer and a shell layer, wherein the material of the core layer comprises lithium iron phosphate material, the shell layer at least partially covers the surface of the core layer, and the material of the shell layer comprises a carbon material, wherein the carbon material contains carbon, oxygen and lithium elements; XPS is used to test the surface elements of the lithium iron phosphate positive electrode material, and the result is 5%<S Li / S C <10%,50%<S C / S O <70%, among which S Li is the area of the characteristic peak of lithium, S C is the area of the characteristic peak of carbon element, S O is the area of the characteristic peak of oxygen element.
6. The method for preparing the lithium iron phosphate positive electrode material according to claim 5, characterized in that: In S2, the conditions of the first sintering are: temperature 500-900°C, time 5-20h; in S4, the conditions of the second sintering are: temperature 300-500°C, time 5-20h.
7. The method for preparing the lithium iron phosphate positive electrode material according to claim 5 or 6, characterized in that: In S3, the mass ratio of the lithium element in the second lithium source to the oxygen element in the second carbon source is 0.1 to 0.
3.
8. The method for preparing the lithium iron phosphate positive electrode material according to claim 5 or 6, characterized in that: In S3, the conditions of the coordination reaction are: temperature 25-50° C., time 2-10 h.
9. The method for preparing the lithium iron phosphate positive electrode material according to claim 5 or 6, characterized in that: In S4, the mass ratio of the lithium element in the third material to the second material is (0.001-0.005):
1.
10. The method for preparing the lithium iron phosphate positive electrode material according to claim 5 or 6, characterized in that: The first carbon source is at least one of polyethylene glycol and glucose; and / or, the second carbon source is at least one of polyethylene glycol, polypropylene glycol, and polydextrose; and / or, the first lithium source and the second lithium source are each independently at least one of lithium hydroxide, lithium hydroxide monohydrate, lithium oxide, and lithium carbonate; and / or, the phosphorus source is at least one of iron phosphate, diammonium phosphate, and phosphoric acid; and / or, the iron source is at least one of iron phosphate, iron oxalate, and ferric oxide; and / or, the M source is at least one of an oxide containing the M element, a nitrate containing the M element, and a carbonate containing the M element.